Synthesis of NIR-II Absorbing Gelatin Stabilized Gold Nanorods and Its Photothermal Therapy Application against Fibroblast Histiocytoma Cells - Adewale Oladipo; Thabang Calvin Lebepe; Sundararajan Parani; Rodney Maluleke; Vuyelwa Ncapayi; Grace It Mwad Mbaz; Sandile Phinda Songca; Tetsuya Kodama; Oluwatobi Samuel Oluwafemi (MDPI AG, 2021)
The excellent photothermal properties of gold nanorods (Au-NRs) make them one of the most researched plasmonic photothermal nanomaterials. However, their biological applications have been hampered greatly due to surfactant-induced cytotoxicity. We herein report a simple synthesis of highly biocompatible gelatin stabilized Au-NRs (gelatin@Au-NRs) to address this issue. The optical and structural properties of the as-synthesized gelatin@Au-NRs were investigated by Zetasizer, Ultraviolet-Visible-Near Infrared (UV-Vis-NIR) spectroscopy, high-resolution transmission electron microscopy (HR-TEM), and Fourier transform infrared spectroscopy (FTIR). The as-synthesized gelatin@Au-NRs were highly crystalline and rod-like in shape with an average length and diameter of 66.2 ± 2.3 nm and 10 ± 1.6 nm, respectively. The as-synthesized gelatin@Au-NRs showed high stability in common biological media (phosphate buffer saline and Dulbecco's Modified Eagle's Medium) compared to CTAB capped Au-NRs. Similarly, the gelatin@Au-NRs showed an improved heat production and outstanding cell viability against two different cancer cell lines; KM-Luc/GFP (mouse fibroblast histiocytoma cell line) and FM3A-Luc (breast carcinoma cell line) compared to CTAB capped Au-NRs and PEG@Au-NRs. An in vitro photothermal therapy study against KM-Luc/GFP showed that gelatin@Au-NRs effectively destroys the cancer cells.